Effects of Antioxidant Vitamin C, E and C+E Supplementation on Plasma Lipid Profiles, Glycemic Control, and Antioxidant Status Among Type 2 Diabetes Mellitus Subjects in Tehran, Iran - Rafighi, Zahra (2011)
Diabetes mellitus (DM) is one of the leading causes of morbidity and mortality in the world. It is by far the most common serious metabolic disorder, with a world-wide prevalence estimated between 1% and 7%. Type 2 diabetes mellitus (T2DM) accounts for over 95% of diagnosed diabetic patients. The present study was designed to assess the effects of antioxidant vitamins C, E and a combination (C+E) on plasma lipid profiles, enzymatic and non-enzymatic antioxidants among T2 DM patients. This study was a randomized, single-blind placebo-controlled clinical trial was conducted on 170 T2DM patients (84 men and 86 women) aged 30–65 years. Data were collected between July 2009 and December 2009 of Institute of Endocrinology and Metabolism, University of Medical Sciences (IUMS). Tehran, Iran. Patients were randomized into four groups, (group C, group E, group C+E, and group placebo) each group receiving one of the followed daily supplements for three months; They were asked to take one capsule after each meal; group C (n=42) (3×266.7 mg vitamin C), group E (n=43) (3×300IU vitamin), group combination of vitamins C+E (n=45) (3×266 vitamin C+ 3×300IU vitamin E), and group placebo (n=40). The results showed that after intervention the mean systolic blood pressure (SBP) were decreased significantly (p=0.008), (p=0.006), (p=0.003) and diastolic blood pressure (DBP) were decreased significantly (p=0.009), (p=0.004), (p=0.017) in C+E and C groups respectively. The results showed an improvement in the glucose levels and HbA1C decreased significantly (p=0.000), (p=0.000), (p=0.001) in groups C, E and C+E respectively as compared to the placebo group. High density lipoprotein (HDL-C) increased significantly (p=0.001), (p=0.000), (p=0.000) in groups C, group E, and C+E, compared to placebo group respectively. Total cholesterol (TC) were significantly (p<0.001) decreased in group C, E and C+E compared with placebo after intervention, respectively. Low density lipoproteins-cholesterol (LDL-C) significantly (p<0.001) decreased in groups C, E and C+E respectively as compared to the placebo group. Triglyceride (TG) decreased significantly (p<0.001) in the groups C, E and C+E compared with placebo respectively. Vitamin C increased significantly (p=0.012), (p=0.001), (p=0.006) in group C, E and C+E compared with placebo groups after intervention respectively. Vitamin E increased significantly (p=0.005), (p=0.006), (p=0.007) in group C, E and C+E compared with placebo groups after intervention respectively. SOD increased significantly (p=0.003), (p=0.007), (p=0.003) in groups C, E, and C+E, compared with placebo group after intervention respectively. GPx increased significantly (p=0.002), (p=0.003), (p=0.003) in group C, E and C+E, compared with placebo group after intervention respectively. It is concluded that co-supplementation of vitamin C and E and also combination of vitamins C+E increased antioxidant enzyme capacity and decreased glucose level HbA1C, hypertension and lipid profiles (LDL-C, TG, and TC) while increased HDL-C. Therefore supplementation of these micronutrients is recommended forthe T2DM patients based on their daily requirements after 12 weeks of intervention as observed from this study.